Slipped capital femoral epiphysis in 17 Maine Coon cats. Issue 1 (January 2017) - Borak, Danilo; Wunderlin, Nadja; Brückner, Michael; Schwarz, Günter; Klang, Andrea
Objectives: From May 2009 to January 2015, 208 Maine Coon cats presented to the Tierklinik Hollabrunn – a small animal referral and first-opinion centre – and 17 (8.17%) cats were diagnosed with a slipped capital femoral epiphysis (SCFE). Over the same time period, 29 (0.67%) of 4348 cats (all breeds) were diagnosed with SCFE. Methods: Clinical and orthopaedic examinations and diagnostic imaging were performed on all affected Maine Coons. Age at first presentation, sex, body weight, body condition score (BCS), unilateral or bilateral manifestation of the disease, activity level and duration of lameness, age at neutering and known family history of disease were recorded. Sixteen of 17 Maine Coons were surgically treated. Surgically removed femoral tissue samples were histologically examined in 13 cases. Results: The mean age at first presentation was 21.47 months; male to female ratio was 16:1; mean body weight was 7.5 kg (range 5.3–9.3 kg); and mean BCS was 5.06/9.0. Seven cats were bilaterally affected; the median duration of decreased activity level and lameness was 2 weeks; mean age at neutering was 7.7 months (range 3.0–12.0 months); and four cats were littermates. Fourteen femoral head and neck ostectomies, eight total hip replacements and one primary fixation were performed. All 13 histologically available samples confirmed the diagnosis of SCFE. Conclusions and relevance: To date, SCFE has been reported only occasionally in Maine Coon cats. However, the results of this study showed that Maine Coons were approximately 12-fold more likely to develop SCFE than the overall population of cats presenting to the Tierklinik Hollabrunn over the same time period. Male sex, neutering, delayed physeal closure and breed-specific high body weight may play an important role in the pathogenesis of SCFE in Maine Coon cats.